Characterizing prehistoric archery: technical and functional analyses of the Neolithic bows from La Draga (NE Iberian Peninsula). (March 2015) - Piqué, Raquel; Palomo, Antoni; Terradas, Xavier; Tarrús, Josep; Buxó, Ramon; Bosch, Àngel; Chinchilla, Júlia; Bodganovic, Igor; López, Oriol; Saña, Maria
Abstract: The discovery in 2012 of a complete yew bow ( Taxus baccata ) in the lakeside Neolithic site of La Draga, together with two more fragmented bows from previous field seasons, are the oldest evidence of archery among farming communities in Europe. This group of bows has allowed different aspects of prehistoric archery to be considered. Firstly with regard to the manufacturing processes of these weapons, which show great uniformity in terms of the raw material used, but some variety in shapes and sizes. Secondly about the socioeconomic significance of weapons in societies which no longer based their economy on hunting and gathering. Highlights: La Draga is a lacustrine site dating from the late sixth millennium cal BC. In this paper we present the three yew bows recovered at la Draga site. The bows are the oldest examples of Neolithic archery documented in Europe. The good preservation allows analyzing aspects of their production and function. We discuss its economic and social role in the frame of Neolithic societies.